Diabetes: how to manage cardiovascular risk in secondary prevention patients - Sarah L Anderson; Joel C Marrs (BioExcel Publishing Ltd, 2022)
Atherosclerotic cardiovascular disease (ASCVD) commonly affects people with type 2 diabetes (T2D). Historically, traditional cardiovascular (CV) risk-lowering therapies in patients with T2D and ASCVD have included antiplatelet agents, blood pressure-lowering therapies, lipid-lowering therapies and healthy lifestyle modifications. In the past decade, multiple antihyperglycaemic agents have emerged as CV risk-lowering therapies in this population as well. This article provides a narrative review on the current non-glycaemic and glycaemic treatment options for CV risk reduction in patients with T2D and ASCVD. The FDA requirement that all new antihyperglycaemic agents undergo cardiovascular outcomes trials has demonstrated increasing evidence to support the role of glucagon-like peptide 1 (GLP1) receptor agonists and sodium-glucose cotransporter 2 (SGLT2) inhibitors as first-line agents for both glycaemic control and CV risk reduction in this population.